Electron physics of vacuum and gaseous devices - Sedlacek, Miroslav (John Wiley & Sons, 1996)
For over fifty years, the electron tube was the dominant component in electronic devices used in communications, industry, and science. By the 1960s, however, the transistor and solid-state technology appeared to render the quaint glowing tubes obsolete.